2010
DOI: 10.1037/a0019993
|View full text |Cite
|
Sign up to set email alerts
|

The road to forgiveness: A meta-analytic synthesis of its situational and dispositional correlates.

Abstract: Forgiveness has received widespread attention among psychologists from social, personality, clinical, developmental, and organizational perspectives alike. Despite great progress, the forgiveness literature has witnessed few attempts at empirical integration. Toward this end, we meta-analyze results from 175 studies and 26,006 participants to examine the correlates of interpersonal forgiveness (i.e., forgiveness of a single offender by a single victim). A tripartite forgiveness typology is proposed, encompassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
526
4
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 586 publications
(587 citation statements)
references
References 164 publications
44
526
4
13
Order By: Relevance
“…Offenses or "wrongs" violate moral boundaries. Forgiveness is usually correlated with higher empathy and lower anger states (Fehr, Gelfand, & Nag, 2010;McCullough et al, 1997). Also, McCullough et al (1998) suggested that relationship closeness might facilitate forgiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Offenses or "wrongs" violate moral boundaries. Forgiveness is usually correlated with higher empathy and lower anger states (Fehr, Gelfand, & Nag, 2010;McCullough et al, 1997). Also, McCullough et al (1998) suggested that relationship closeness might facilitate forgiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Also, McCullough et al (1998) suggested that relationship closeness might facilitate forgiveness. Thus, multiple characteristics of the forgiver, the transgressor, the relationship and the offense affect whether forgiveness is experienced (for a review, see Fehr et al, 2010). Considering the different conceptualizations and the high interest in forgiveness, diverse measures have been developed to assess several types and aspects of forgiveness (for a review, see Worthington, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Second, evidence has shown that victims who are close to their perpetrators or who are concerned about breaching social or moral standards are likely to forgive, yet the literature also has demonstrated that the egregiousness of perpetrators' actions is negatively related to forgiveness (Fehr, Gelfand, & Nag, 2010). Although these associations with forgiveness are in opposite linear directions, we suggest that they have the potential to function together.…”
mentioning
confidence: 67%
“…Neuroticism was controlled because more neurotic individuals may be more likely to recall and report negative incidents (cf. Blaney, 1986) and less likely to engage in forgiveness (Fehr et al, 2010).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation